STATIC-PERFORMANCE BASED COMPUTER-AIDED DESIGN OF A DDV AND ITS SENSITIVITY ANALYSIS - Mookherjee, Saikat; Acharyya, Sanjib; Majumdar, Kamalesh; Sanyal, Dipankar (International Journal of Fluid Power, 2001)
Direct Drive valves (DDV) are gaining increasing acceptability for their simple configuration, low leakage, and low cost. Two major components of the present single-stage DDV are a spool valve and a linear force-motor. The objective of the present investigation was to formulate a design methodology and a static performance simulation tool for the DDV. The present work includes lumped and chiefly one-dimensional, non-linear field modelling of flow through the spool valve and magnetic flux in the motor. Detail modelling has been done only for leakage flow in the spool-bushing radial clearance of the spool valve, since it has critical bearing in the performance analysis. A computer-aided tool for designing a single stage valve, based on some additional simplifying assumptions of the lumped model, has been pre-sented. The static performance algorithm was developed on SIMULINK, without invoking the design-level simplifica-tions. The simulation tool has been used to carry out a design validation against the known performance of Moog Series D633 valve. Different designs of the valve, corresponding to different actuation specifications were obtained, and their static performances have been investigated. Also a sensitivity analysis has been carried out to study the effects of trac-tive air gap area ratio in the motor and port lap conditions in the spool valve.